Genetic relatedness of clinical and environmental Acinetobacter baumanii isolates from an intensive care unit outbreak - Abiola Senok; Ghada Garaween; Adeola Raji; Harish Khubnani; Garwin Kim Sing; Atef Shibl (Journal of Infection in Developing Countries)
Introduction: Determination of microbial genetic relatedness is important for improving efficiency of infection control measures during hospital outbreaks. This study aimed to analyze the clonal relationships of clinical and environmental Acinetobacter baumannii strains isolated during an outbreak in the intensive care unit (ICU) of a secondary care hospital in Saudi Arabia. Methodology: Twelve clinical and fourteen environmental A. baumannii isolates identified during an outbreak in February 2013 in the 14-bed adult  intensive care unit of a tertiary care hospital in Riyadh, Saudi Arabia, were studied. Bacterial identification and antimicrobial susceptibility testing were carried out using Microscan Walkaway 96 automated system. Determination of clonal diversity was investigated by repetitive-sequence-based polymerase chain reaction (rep-PCR) with the semi-automated DiversiLab system. Results: The majority of the clinical isolates were from endotracheal tube aspirates (n = 9), one from a wound swab and two were from urine and sputum, respectively. Environmental isolates were from bed railings (n = 10) and with one each from curtain, stethoscope, computer mouse and telephone. Isolates were categorized into 6 clusters (Groups 1-6). Most of the isolates were associated with two clusters namely Groups 2 (n = 11) and 3 (n = 9). All isolates were multidrug resistant showing resistance to three or more classes of antibiotics. One clinical strain from Cluster 3 was resistant to colistin (MIC > 4ug/ml). Conclusion: This outbreak was caused by two clonal groups of multidrug resistant A. baumannii. The presence of multiple environmental clones was suggestive of environmental source dissemination via healthcare workers within the ICU.